Quantitative Eco-nomics:: How sustainable are our economies? by Peter Bartelmus - Tiburcio, James Augusto Pires (Sustainability in Debate, 2011)
BARTELMUS, Peter. Quantitative Eco-nomics: How sustainable are our economies? Dordrecht Springer Science Business Media B.V. 2008. 329 p. ISBN 978-1-402069666.